"#NieMojaAriel". Tokenizm, reprezentacja i „rasa” we współczesnej amerykańskiej popkulturze - Górny, Antoni (Zagadnienia Rodzajów Literackich, 2025)
The article discusses the recent controversy surrounding the casting of a Black actress in the lead role in the live-action remake of the Disney classic The Little Mermaid (2023), placing this event in the context of the history of “racial” representation in American film. Taking its cue from the widespread identification of the new Ariel as a token Black character, it explores the significance of “blind casting” in contemporary films as an evolution of the practice of tokenism in post-war American cinema. A feature of the “race problem” film, tokenism has become commonplace in 20th and 21st century, playing a major role in defining the idea of Blackness and of “racial” equality for American audiences after World War II. However, it has also fostered a drastically simplified notion of Black identity, as well as of racism as a social practice. The logic of tokenism persists in many recent American films where the subject of racism is addressed directly (as in Green Book, 2018), but it can also be seen in texts that are not explicitly about “race.” The article argues that controversies such as #NotMyAriel represent a rearticulation of these established practices of “racial” casting, where racism is no longer represented in the film, but rather plays out in debates about the validity of “racial” representation taking place on the Internet.